2006
DOI: 10.1073/pnas.0602503103
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1 positively regulates stomatal opening in response to blue light in Vicia faba

Abstract: phototropin ͉ H ϩ -ATPase ͉ light signaling ͉ phosphorylation͞ dephosphorylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 54 publications
3
109
0
Order By: Relevance
“…Fluorescent images were obtained using a confocal laser-scanning microscope (Digital Eclipse C1; Nikon) 14 . The wavelengths of excitation and emission for GFP were 488 nm and 515-530 nm, and those for chlorophyll fluorescence were 543 and 590 nm long-pass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent images were obtained using a confocal laser-scanning microscope (Digital Eclipse C1; Nikon) 14 . The wavelengths of excitation and emission for GFP were 488 nm and 515-530 nm, and those for chlorophyll fluorescence were 543 and 590 nm long-pass.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanisms by which phototropin transduces the light signal into downstream responses are largely unknown. In guard cells, the driving force for stomatal opening is generated by plasma membrane H þ -ATPases that are activated via phototropins [11][12][13] , and it has been established that protein phosphatase 1 (PP1) mediates the signalling between these two molecules 14 . However, the initial signalling event that couples photoreception to activation of the H þ -ATPase has yet to be clarified.…”
mentioning
confidence: 99%
“…A candidate for ABA-binding protein that protein phosphatase 1 (PP1), a major member of the PPP family of Ser/Thr protein phosphatases, mediates the signaling between phototropins and H + -ATPase in guard cells. 86 Therefore, ABA is likely to inhibit the signaling molecule(s), including phototropins, PP1, H + -ATPase and other unidentified components.…”
Section: Aba Sensing and Signalingmentioning
confidence: 99%
“…The activated phototropins transmit the signal to plasma membrane H + -ATPase for its activation (Christie, 2007). In addition, it was demonstrated that phosphatase 1 (PP1, Ser/Thr protein phosphatase) mediates the signal between phototropins and H + -ATPase in guard cells (Takemiya et al, 2006). It is known that ABA inhibits blue light dependent proton pumping by plasma membrane H + -ATPase (Zhang et al, 2004).…”
Section: Physiological Rolesmentioning
confidence: 99%